Drivers of The Organic Mushroom Market in Kathmandu Valley: A Dual-Perspective Analysis of Consumer Willingness-To-Pay and Producer Viability - Sharma, Dibya; Chaulagain, Bidur P. (Nepalese Journal of Agricultural Sciences, 2026)
The demand for safe and organic food is rising in urban Nepal, but the market for organically grown mushrooms remains underdeveloped. Understanding consumer behavior and producer readiness is crucial for market development. This study aimed to assess mushroom consumption patterns, awareness, access disparities, and willingness to pay (WTP) for organic mushrooms in Kathmandu Valley, integrating perspectives from both consumers and producers. A mixed-methods approach was employed. Data were collected from 150 consumers through a structured online survey and from 10 producers/traders via in-person interviews. Analysis involved descriptive statistics, chi-square tests, binary logistic regression, and cost-benefit analysis. A vast majority (94.7%) of respondents consumed mushrooms, primarily driven by taste and nutritional value. Awareness of organic mushrooms was high (88%) and significantly associated with education level (p